Sky-blue thermally activated delayed fluorescence polymers by using a conjugation-confined poly(aryl ether) main chain. Issue 16 (7th April 2021) - Chen, Tianheng; Chen, Zhanxiang; Ni, Fan; Xie, Guohua; Yang, Chuluo
Abstract : A series of sky-blue TADF polymers were developed by applying a bipolar poly(aryl ether) main chain, and solution-processed OLEDs with these polymers doped into the host DMAC-DP-CZ showed high external quantum efficiencies of up to 14.5%. Abstract : The development of thermally activated delayed fluorescence (TADF) polymers has attracted wide attention due to their application in solution-processed organic light emitting diodes (OLEDs). However, high-performance blue TADF polymers are still scarce compared with their green and red counterparts. In this work, we report a series of sky-blue TADF polymers by using a carbazole-based poly(aryl ether) main chain. This series of polymers are convenient to be synthesized and purified, and the number-average molecular weights of these polymers were determined to be above 50 000 g mol −1 with polydispersity indices below 2. Benefiting from the conjugation-confined polymer backbone, a high triplet energy level of 2.81 eV can be achieved for this main chain. By grafting sky-blue TADF emitters onto the side chain, the TADF channel was successfully established for these developed polymers. The resulting solution-processed OLEDs successfully achieved a maximum external quantum efficiency of 14.5% with the Commission Internationale de L'Eclairage coordinates of (0.18, 0.34), which is comparable with those of the devices using sky-blue phosphorescent polymers.